Enhancing Students’ Reading Comprehension and Reading Efficiency in the UTBK English Literacy Subtest through Skimming and Scanning Techniques - Aulia Ukhtin (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study aims to examine the effectiveness of skimming and scanning techniques in enhancing students' reading comprehension and reading efficiency in the English literacy subtest of Ujian Tulis Berbasis Komputer (UTBK). The study employed a quantitative approach using a quasi-experimental design with a pre-test and post-test. The participants consisted of 30 Grade 12 students enrolled in a private tutoring institution. The instrument used was a UTBK style reading comprehension test consisting of 20 multiple-choice questions completed within 20 minutes. The results revealed a significant improvement in students' reading performance, with the mean score increasing from 11.13 in the pre-test to 16.03 in the post-test. The paired sample t-test indicated a statistically significant difference between pre-test and post-test scores (t=18.42, p <0.001). In addition, students demonstrated improved reading efficiency as reflected in reduced completion time and increased accuracy. These findings suggest that skimming and scanning techniques are effective in promoting strategic reading behaviour, enabling students to process texts more efficiently under time constraints. The study highlights the importance of integrating strategy-based instruction in preparing students for high-stakes English literacy assessments.